المجاهد عبد القادر بريك المدعو البوياحي و دوروه في الثورة التحريرية - سبوعي, فتحي; تريكي, عبدالحميد (جامعة الوادي - University of Eloued, 2023)
In this memory, we approach the biography of Al-MujahidAbd-KadirBrik, known as "Al-Bouayahi," and his role in the liberation revolution beginning from the milieu of his origin and his activity, which varied between the deserts of south-eastern Algeria and southern Tunisia, then the introducing him with his family, who practiced a life of stability and nomadism from the 1920s to the 1940s. He spent most of his life grazing between his maternal uncles and the throne of Al-Buwayhi's children in Tunisia after his trip in 1950 AD, which caused a quantum leap in his life thanks to his training in liberal thought in favor of the Tunisian revolution, and his participation in it, and his teaching of reading, writing, and arithmetic. Then he followed his participation in the Algerian revolution in the southeastern region of the first region and his activity as a soldier under the leadership of Al-Jilani bin Omar and TalebLarbiGammoudi, after his investiture as the leader under the army of TalebLarbiGammoudi and his revolutionary activity as the leader of a platoon in the same region, which became the fourth region of the sixth Wilaya. And his positions on the dispute between TalebLarbi and his enemy. Then his activity in the fifth region of the first wilaya under the leadership of Mahmoud Ginz, then his participation in the battle in the sixth wilaya, his transfer to the Garn Halfaya training center under the leadership of Abd al-MajidAllehm, and his transfer to the desert region on the Libyan frontier under the leadership of al-TayyibFarhat, and his activity there until the restoration of national sovereignty in the year 1962. Then a summary of his life after the restoration of national sovereignty to death.
مذكرة ماستر تاريخ تخصص المغرب العربي المعاصر
Keywords: البوياحي– عبد القادر – المنطقة الخامسة – الولاية الأولى; Al-buwayahi-Abdulkader-fifth region-first state